A case grafted with polyglycolic acid sheets and fibrin glue for protection after temporary resection of a metastatic cervical skin tumor. Issue 2 (April 2018) - Matsuzuka, Takashi; Suzuki, Masahiro; Ikeda, Masakazu; Sato, Kaoru; Fujimoto, Junko; Hosaka, Rumi; Tanji, Yuko; Soeda, Shu; Murono, Shigeyuki
Abstract: The aim of this case report was to evaluate the usefulness of a grafting with polyglycolic acid sheet and a fibrin glue spray (PGA sheet grafting) after resection of a cervical skin tumor. A 61-year-old woman presented with left cervical skin tumor resistance to chemo-radiotherapy. She had been undergoing multimodal therapy for ovarian serous papillary adenocarcinoma for the previous six years. Although she had a poor general condition and a cervical skin tumor of 9 cm in diameter, which was painful and easy bleeding, had offensive smell, she hoped to return to her job. Under local anesthesia, resection was performed, and PGA sheet grafting were used to shield the skin defect. After resection, she was relieved from pain, and could stay home without daily wound treatment. One and half months after resection, the wound was almost epithelialized. The PGA sheets consist of soft, elastic, nonwoven fabric made of PGA. In recent years, PGA sheet grafting has been widely used in the reconstruction and was chosen to shield the skin defect for this case. PGA sheet grafting after resection of cervical skin tumor can be an acceptable method for palliative care to relieve pain, bleeding, offensive smell, and ugly appearance.